Risk factors affecting progression and course of primary open-angle glaucoma in patients with different disease stages (multicenter study) - N.E. Fomin; P.Ch. Zavadskiy; A.V. Kuroyedov; A.V. Seleznev; Z.M. Nagornova; D.A. Baryshnikova; R.V. Avdeev; A.M. Getmanova; I.A. Glushnev; A.A. Gusarevich; D.A. Dorofeev; S.V. Kosmynina; et al. (РМЖ "Клиническая офтальмология")
N.E. Fomin1,2, P.Ch. Zavadskiy3, A.V. Kuroedov1,2, A.V. Seleznev4, Z.M. Nagornova4, D.A. Baryshnikova5, R.V. Avdeev6, A.M. Getmanova7, I.A. Glushnev8, A.A. Gusarevich9, D.A. Dorofeev10, S.V. Kosmynina11, O.S. Myakonkaya12, N.A. Rebenok8, Yu.I. Razhko8, I.I. Semenova13, T.V. Chernyakova14 1P.V. Mandryka Military Clinical Hospital, Moscow, Russian Federation 2Pirogov Russian National Research Medical University, Moscow, Russian Federation 3 Karelia Ophthalmological Center, Petrozavodsk, Russian Federation 4Ivanovo State Medical Academy, Ivanovo, Russian Federation 5Sectoral Clinical Diagnostic Center of the PJSC "Gazprom", Moscow, Russian Federation 6 N.N. Burdenko Voronezh State Medical University, Voronezh, Russian Federation 7 Bryansk Regional Hospital No. 1, Bryansk, Russian Federation 8Republican Scientific Practical Center of Radiation Medicine and Human Ecology,   Gomel, Republic of Belarus 9 Clinical Hospital "RZD-Medicine" of the city of Novosibirsk, Novosibirsk, Russian Federation 10 City Clinical Hospital No. 2, Chelyabinsk, Russian Federation 11 P.A. Bayandin Murmansk Regional Clinical Hospital, Murmansk, Russian Federation 12Volgograd Branch of the S. Fyodorov Eye Microsurgery Federal State Institution,   Volgograd, Russian Federation 13 Mogilev City Hospital of the Emergency Medical Care, Mogilev, Republic of Belarus 14 Multidisciplinary Medical Center of the Bank of Russia, Moscow, Russian Federation Aim: to identify certain risk factors and their associations, which determine the prognosis of primary open-angle glaucoma (POAG) in patients with different disease stages. Patients and Methods: the final protocol of this clinical research combines multicenter study included the results of dynamic follow-up of 293 patients (293 eyes) with different stages of POAG. The mean age at the time of diagnosis was 65 (59; 70) years. The duration of verified POAG history was 3 (1; 6) years. Age, medical history, disease stage, IOP levels, IOP-lowering medications, comorbidities, other (social) factors (in total, 23 entities considered potential causes of refractory glaucoma) were investigated. All participants were divided into two groups (non-refractory glaucoma and refractory glaucoma) that included six subgroups according to current guidelines on achieving target IOP in various treatment approaches. Results: at the time of verified diagnosis and final examination of POAG patients, IOP levels were higher in the refractory glaucoma group and patients with advanced glaucoma (p<0.001). The most common risk factors, comorbidities, and other variables characterizing refractory glaucoma were pseudoexfoliative syndrome/PEX (53.5%), pigment dispersion syndrome/PDS (16.7%), dry eye disease/DED (38.6%), high myopia (7.9%), coronary heart disease/CHD (40.3%), smoking (16%), and disability resulting from a general illness (12.6%). The rate of these entities varied from 11.1% to 69.4%, being most common in the refractory glaucoma group. Refractory glaucoma patients had a tendency to a slow return to topical treatment in the early postoperative period after glaucoma surgery, despite the lack of achieving target IOP. Conclusion: our study has demonstrated that IOP levels at the time of verified diagnosis directly correlate with the stage of newly diagnosed glaucoma and IOP levels in the setting of glaucoma treatment and predetermine future refractory disease. Moreover, PEX, PDS, DED, CHD, prior myocardial infarction, and disability resulting from a general illness are additional factors determining POAG resistance to treatment. Keywords: glaucoma, intraocular pressure, refractory, risk factors, progression. For citation: Fomin N.E., Zavadskiy P.Ch., Kuroedov A.V. et al. Risk factors affecting progression and course of primary open-angle glaucoma in patients with different disease stages (multicenter study). Russian Journal of Clinical Ophthalmology. 2022;22(2):80–90 (in Russ.). DOI: 10.32364/2311-7729-2022-22-2-80-90.